Avaliação in vitro da atividade anti Trypanosoma cruzi de um derivado de 1,2,4-oxadiazol - Rocha, Yasmim Mendes (2022)
Chagas disease is also a neglected disease, prevalent and endemic in Latin America, but present in Europe and North America. The main treatment used is benznidazole, but its difficulty is variable in chronic and high toxicity. In this context, there is a need to develop new therapeutic agents. The five-membered 1,2,4-oxadiazole heterocyclic ring has attracted attention for its unique properties and a broad spectrum of known biological activities, making it a potential candidate for the development of new drugs. Thus, the aim of this study was to evaluate the activity of the molecule N-cyclohexyl-3- (3-methylphenyl)-1,2,4-oxazol-5 (molecule 2) in the different phases of the life cycle of the Y strain of Trypanosoma cruzi, as well as its mechanisms of action and theoretical approach, found a computational analysis. By prediction ADME/the result itself, with permeability capacity and intestinal absorption capacity (92), different from benznidazole (92%), in addition to presenting with good penetration capacity in the hematoma (0.09), unlike the barrier reference (-0.863). Results by computational method, an interaction of molecule 2 chosen as enzymes parautainase, TcGAPDH, target draw of charge and affinity in the three processes. In addition, the evaluation of cytotoxicity in LLCMK2 cells (1000 - 7μM) was performed by reducing MTT by 25%, which revealed a 25% viability in all possible methods. In tests with epimastigotes (24, 48 and 72h), trypomastigotes and amastigotes (24h), the study compound showed a concentrated time-dependent effect. The evaluation of the effect between cells and number of new cells (30 μM) showed no number of affected cells and no reduction of small cells (30120 μM). By flow cytometry, the mechanism of action of the molecule (2) was investigated and alterations suggestive of events or late apoptosis were observed, with an increase in the reactive species of cytoplasmic functioning and mitochondrial dysfunction. The electronic scanning machine, which can be modified, can modify the necessary process characteristics of epimastigotes. In this context, Ncyclohexyl-3-(3-methylphenyl)-1,2,4-oxadiazol-5-amine opens perspectives for the development of new, more selective antichagasic agents.